UJI EKSPERIMENTAL PENGARUH VARIASI PENAMBAHAN ZEOLIT PADA PEMBUATAN BAHAN BAKAR ALTERNATIF DARI OLI BEKAS DENGAN METODE DESTILASI - Imron, Imron Musthofa; Rusuminto Syahyuniar; Kurnia Dwi Artika; Hajar Isworo; Reza Taufiqi Ivana (POLITALA PRESS, 2023)
Used oil waste increases every year, engine maintenance waste will increase. Waste oil is classified as B3 waste which requires special treatment. In the development of cities and regions, the amount of fuel used continues to increase due to the increasing number of vehicles and car engines. Even in rural areas, you can find small companies, one of which uses oil. In other words, the distribution of palm oil waste is very wide, ranging from big cities to rural areas in Indonesia. The research process was to convert used oil into constant-temperature heating oil by using a distillation process. The method used aims to find out the best results at temperatures and variations of the zeolite catalyst. 350oC produces 1005 ml of fuel in 90 minutes. While the lowest results were obtained without using a zeolite catalyst to produce 105 ml of fuel. Thus, the use of zeolite is easy and effective in weakening the bonds of the hydrocarbon chains in the oil.